Determination of variation of slot permeance in induction machines including slot bridge saturation - Guldemir, H. (University of Split, 2000)
The paper uses finite element analysis for obtaining permeance variation around the airgap and its harmonic content for a squirrel-cage closed-slot induction motor. The paper also presents a similar solution for the variation in slot permeance which takes into account the core saturation due to the nonlinear characteristics of the magnetic material and the saturation due to induced rotor bar currents which are of great interest, which has not been available so far: The permeance variation is derived from the stored energy which is obtained using the finite element (FE) field solution. The permeance distribution is then decomposed into the harmonic content by using Fast Fourier Transform. The dependence of the harmonic components on the rotor current is also given.
Keywords: Airgap; Induction motor; Permeance; Slot; Slot bridge saturation